Effect of baking and fermentation on the stable carbon and nitrogen isotope ratios of grain‐based food. (6th April 2015) - Bostic, Joshua N.; Palafox, Sherilyn J.; Rottmueller, Marina E.; Jahren, A. Hope
Abstract : Rationale: Isotope ratio mass spectrometry (IRMS) is used extensively to reconstruct general attributes of prehistoric and modern diets in both humans and animals. In order to apply these methods to the accurate determination of specific intakes of foods/nutrients of interest, the isotopic signature of individually consumed foods must be constrained. For example, 86% of the calories consumed in the USA are derived from processed and prepared foods, but the relationship between the stable isotope composition of raw ingredients and the resulting products has not been characterized. Methods: To examine the effect of common cooking techniques on the stable isotope composition of grain‐based food items, we prepared yeast buns and sugar cookies from standardized recipes and measured bulk δ 13 C and δ 15 N values of samples collected throughout a 75 min fermentation process (buns) and before and after baking at 190°C (buns and cookies). Simple isotope mixing models were used to determine if the isotopic signatures of 13 multi‐ingredient foods could be estimated from the isotopic signatures of their constituent raw ingredients. Results: No variations in δ 13 C or δ 15 N values were detected between pre‐ and post‐baked yeast buns (pre: –24.78‰/2.61‰, post: –24.75‰/2.74‰), beet‐sugar cookies (pre: –24.48‰/3.84‰, post: –24.47‰/3.57‰), and cane‐sugar cookies (pre: –19.07‰/2.97‰, post: –19.02‰/3.21‰), or throughout a 75 min fermentation process in yeast buns. Using isotopic mass balance equations, the δ 13 C/δ 15 N values of multi‐ingredient foods were estimated from the isotopic composition of constituent raw ingredients to within 0.14 ± 0.13‰/0.24 ± 0.17‰ for gravimetrically measured recipes and 0.40 ± 0.38‰/0.58 ± 0.53‰ for volumetrically measured recipes. Conclusions: Two common food preparation techniques, baking and fermentation, do not substantially affect the carbon or nitrogen isotopic signature of grain‐based foods. Mass‐balance equations can be used to accurately estimate the isotopic signature of multi‐ingredient food items for which quantitative ingredient information is available. Copyright © 2015 John Wiley & Sons, Ltd.